THE CORONAVIRUS IN LIBERAL AND ILLIBERAL DEMOCRACIES AND THE FUTURE OF GLOBALIZED WORLD - BRZECHCZYN, KRZYSZTOF (Society Register, 2020)
The aim of this article is to compare the effectiveness of two political systems: liberal democracy and illiberal democracy in fighting the coronavirus pandemic. The analysis has been carried out on the basis of the theoretical assumptions and conceptualization of non-Marxian historical materialism. In the first part of my article, I present the concept of ‘regulative credit” which has been introduced in that theory. In standard socio-political conditions, the growth of power regulations is usually contested by citizens. However, in a situation of danger, when social order is undermined, citizens support the authorities’ extraordinary regulations. This social support, called regulative credit, lasts as long as the danger persists. In chapter two, I characterize shortly liberal and illiberal democracies. In liberal democracy, there is a balance between different branches of power, and citizens share a socio-political consciousness of the individualistic type. In illiberal democracy, the executive branch of power – although it has been democratically chosen – has an advantage over the two other kinds of power, and citizens share a socio-political consciousness of the collectivist type. Those differences result in diverse reactions of the authorities to a situation of threat. The political authorities of an illiberal democracy react faster in comparison with the political authorities in liberal democracies that react slower. Also, the attitude of citizens toward the introduced restrictions varied. Societies of illiberal democracies are more self-disciplined and more willing to accept restrictions from above. Whereas societies of liberal democracies are more individualistic and less willing to accept limitations. In the fourth part of my paper, I analyze briefly the influence of the pandemic on globalization processes and on the relations between the EU and the nation states in Europe. In the summary (chapter five), I predict that the mass use of modern technologies to control social life and strengthening of the sovereignty of nation states will be the two most important effects of the pandemic.